DIAGNOSIS AND TREATMENT OF MYOCARDITIDES - S. N. Tereshchenko; I. V. Zhirov; V. P. Masenko; O. Yu. Narusov; S. N. Nasonova; A. N. Samko; O. V. Stukalova; M. A. Shariya (Евразийский Кардиологический Журнал, 2019)
.